การบัญชีความรับผิดชอบต่อสังคมและสิ่งแวดล้อม : ความสำเร็จองค์กรอย่างยั่งยืน - ทวีจันทร์, สุภัทรษร (Naresuan University Journal: Science and Technology (NUJST); Vol 21 No 1 (2013): January-March 2013)
การบัญชีสังคมและสิ่งแวดล้อม เป็นการบัญชีที่ให้ความสำคัญกับการเปิดเผยข้อมูลเกี่ยวกับสภาพแวดล้อม เป็นวิวัฒนาการทางการ บัญชีแขนงหนึ่งที่นักบัญชีสมัยใหม่ได้พัฒนาขึ้นมา เพื่อรายงานเกี่ยวกับต้นทุนและผลประโยชน์อันเกิดจากกิจกรรมขององค์กรที่ส่งผล กระทบต่อชุมชน ทั้งที่เป็นข้อมูลด้านการเงินและข้อมูลที่ไม่เกี่ยวกับการเงิน เนื่องจากผลกระทบของปัญหาสิ่งแวดล้อมเป็นประเด็นสำคัญ ต่อภาพลักษณ์องค์กรที่จำเป็นอย่างยิ่งต่อการนำมาตรวจสอบและควบคุมอย่างจริงจัง หากการบัญชีสังคมและสิ่งแวดล้อมมีมาตรฐาน กำหนดระบบที่ชัดเจน เหมาะสม จะมีบทบาทสำคัญที่จะช่วยในการปรับปรุงระบบบัญชีได้ เนื่องจากระบบบัญชีที่มีอยู่สามารถรองรับได้ เพียงต้นทุนที่เกิดขึ้นจริง หรือรายการที่มีความเป็นไปได้ค่อนข้างแน่นอนในการที่กิจการจะได้รับหรือเสียประโยชน์เชิงเศรษฐกิจเท่านั้น หากองค์กรสามารถบริหารจัดทำและนำเสนอต่อสาธารณชนได้ จะทำให้ผู้บริหาร ผู้มีส่วนได้เสีย ตลอดจนผู้ถือหุ้น สามารถวางแผน วิเคราะห์ และตัดสินใจเชิงเศรษฐกิจเพิ่มขึ้น ประกอบกับองค์กรสามารถสะท้อนถึงจิตสำนึก ความรับผิดชอบที่มีต่อสภาพแวดล้อมในสังคม ซึ่งเป็นปัจจัยสำคัญที่มีอิทธิพลต่อการดำรงอยู่อย่างยั่งยืนขององค์กรต่อไป           Coincidentally, the social accounting disciplinary sciences from accounting system being indispensable factor element toward data disclosure reveal capability and environment. Also, this revolution of accounting is one of the integral part area dimensions from neo accountant official proliferation so long so as to report relevant with cost of production & utility advantage impact with organization activity and effect influential community. Significantly, financial data contributed with none relevance financial aspect on account of environment impact problem seriously in issue with corporate image culture. Essentially, the establishment of control and monitoring system initiated with rigid measurement; consequently, environment accounting system still pinpointed with necessary revised improvement of accounting system. According to accounting system has appeared which supported only actual cost and certain listing about benefit and non-benefit of economic. In the event if, organizations can management and presentation to public leading to executive, stakeholder and shareholder will be able to increase their planning, analytical, and decision making of economic. In additional, to reflects environment responsibility was important factor including survivor potentially sustainability of organization so far
Keywords: การบัญชีสังคมและสิ่งแวดล้อม, การเปิดเผยข้อมูล, ข้อมูลด้านการเงินและไม่ใช่การเงิน, Social and Environmental Accounting, Disclosure Information, Financial and Non-Financial Information